Low‐Intensity Focused Ultrasound‐Responsive, Phase‐Change Nanodroplets to Remodel Macrophage Polarization and Enhance PD‐L1 Blockade Therapy - Qin Zhang; Ci Yin; Junjie Liu; Hua Yang; Yanping Zhang; Qiaoxi Qin; Nianhong Wu; Rui Tang; Yuting Cao; Min Zheng; Hongye He; Hongmei Dong; et al. (Small Structures)
Immune checkpoint blockade (ICB) therapy is a promising treatment that has shown significant effects in certain refractory and advanced cancers. However, not all patients respond to ICB therapy. The tumor microenvironment (TME) helps tumors evade immune surveillance and attack, contributing to the low response rate to ICB therapy. M1 macrophages primarily exert antitumor effects within the TME, whereas M2 macrophages support tumor growth and immune evasion through various mechanisms, making them a crucial component of the TME. To reduce M2 macrophages, mitigate TME, and ultimately enhance ICB therapy, perfluoropentane (PFP) is used as the phase‐change material and hematoporphyrin monomethyl ether is incorporated into the nanodroplets (NDs). With mannose modification on their surface, these NDs can effectively target M2 macrophages, denoted as MPH@NDs. When exposed to low‐intensity focused ultrasound, MPH@NDs cause mechanical injury and produce reactive oxygen species. This will lead to remodeling of the distribution of macrophages in the TME, transforming it into a proinflammatory microenvironment. This enhances cytotoxic T lymphocytes accumulation in tumors, remodels TME, and improves PD‐L1 immunotherapy efficacy. MPH@NDs demonstrate promising potential in remodeling the TME, enhancing ICB therapy, and suppressing tumor growth and distant metastasis.